Interlaboratory Testing for High‐Temperature Power Generation Characteristics of a Ni‐Based Alloy Thermoelectric Module. Issue 11 (18th September 2020) - Ziolkowski, Pawel; Chetty, Raju; Blaschkewitz, Przemyslaw; Ohta, Michihiro; Yamamoto, Atsushi; Müller, Eckhard
Abstract : Standardization of metrology for thermoelectric generator modules (TEMs) is a necessary step toward industrialization of thermoelectric applications. Unspecified uncertainty budgets of the widely used custom‐built characterization facilities seem insufficient to validate technological developments, industrial benchmarks, or allow sound conclusions in scientific studies. Particularly, works on high‐temperature TEM have to be supported by suitable characterization techniques. This shall accelerate progress toward product releases for thermoelectric energy conversion. Herein, a Ni‐based alloy TEM is reported, which is developed at the National Institute of Advanced Industrial Science and Technology (AIST) as a prospective standard reference TEM. Comparative measurements at AIST and the German Aerospace Center (DLR) demonstrate the high repeatability and precision of custom‐built TEM characterization facilities at AIST and DLR. Tests at elevated temperatures up to 773 K hot side temperature and 450 K temperature difference reveal excellent accordance of electric measurands with a standard deviation <0.3% for the open‐circuit voltage and <0.85% for electric resistance and maximum power output. Deviations of the heat flow measurement of up to 7.22% arise from individual uncertainties of the used characterization methods and point to the importance of standardization for TEM metrology. Abstract : Herein, the characterization of a Ni‐based thermoelectric generator module (TEM) is reported, which is developed at the National Institute of Advanced Industrial Science and Technology (AIST). Comparative measurements at AIST and the German Aerospace Center (DLR) demonstrate the high repeatability and precision of custom‐built TEM characterization facilities at AIST and DLR with excellent accordance of measurands.